PELATIHAN PENYUSUNAN STRATEGI BISNIS MENGGUNAKAN ANALISIS SWOT PADA USAHA MIKRO KECIL MENENGAH (STUDI KASUS UMKM TANGERANG SELATAN, BANTEN) - Vindiana, Afina Putri; O., Annurdiya Rosyidta P.; Tampubolon, Edward Sahat P.; Premana, Premana; Apriyanti, Riska; Husin, Sabrina Virgi (Jurnal Abdi Insani, 2024)
With the increasing number of SMEs, business competition among SMEs is intensifying, requiring business owners to develop targeted strategies to survive. Business strategies can be formulated by first analyzing a business's potential and weaknesses, then leveraging the potential and addressing the weaknesses. SMEs in South Tangerang face issues such as a lack of knowledge regarding strategic business analysis and an understanding of their strengths, weaknesses, threats, and opportunities. This has resulted in a decrease in monthly revenue for these SMEs. One solution to address these issues among SMEs in South Tangerang is a community service initiative conducted by lecturers and students from the Institut Teknologi Indonesia. This initiative involves training SMEs in strategy formulation using SWOT analysis. SMEs are educated on what SWOT analysis is and guided in identifying the strengths, weaknesses, opportunities, and threats in their businesses. After conducting a SWOT analysis, targeted strategies can be formulated by each SME. From the community's perspective, this activity results in increased knowledge among SME owners in analyzing their business's strengths, weaknesses, threats, and opportunities using the SWOT approach. From an academic perspective, this activity benefits lecturers and students by providing a learning platform and potential research opportunities through case studies of problems faced by SMEs in South Tangerang. As a result of the SWOT analysis training, 90 SMEs in South Tangerang have participated in the training to develop business strategies based on the SWOT approach. With the implementation of these strategies, it is hoped that SMEs will achieve their best business potential and experience an increase in revenue.